Caracterização físico-química e fúngica das silagens de milho utilizadas na alimentação de bovinos leiteiros na microrregião Oeste do Paraná - Fornari, Josias Luis (2019)
The diversification of dairy production systems (SPL) is characterized by distinct characteristics that make it difficult to standardize production systems. In the case of nutrition it is not different, but due to climatic issues and the very technification of the production systems, the use of preserved bulky foods has been an increasingly present reality in the nutrition of dairy cattle. The purpose of this study was to characterize the corn silages used to feed dairy cattle in the municipalities of Marechal Cândido Rondon, Mercedes, Quatro Pontes and Toledo, which are part of the western microregion of Paraná. Initially, semi-structured guide questionnaires were applied to survey productive characteristics and productive management in 190 dairy production systems. From these results clusters formation techniques were employed. Four homogeneous and distinct groups were defined. From the four groups, representative percentages of each group were selected for collection and evaluation of the silages, totaling 63 dairy production systems, of which only 45 SPL provided silage to the animals during the collection period. The material collections were carried out in the silo panel along with a questionnaire about silage storage characteristics such as time closed, types of fence and inoculant use. Physical analyzes such as density, temperature, dimensions, particle size were carried out "in locu", already for chemical and fungal analyzes the material was collected and analyzed in the laboratory. The bromatological variables were used for a new analysis of clusters separating the SPL in 6 homogeneous and distinct groups. It was observed in the present study that 96% of the SPL use food conserved in animal feed along with problems of confection as the sealing of the material where many producers make the superior seal only, even with storage of the material made in the ground directly. The temperatures of the silo panels were much higher than the ambient temperatures, symbolizing the possible development of microorganisms in the silage. For both silages the density was below the recommended one, demonstrating failure in the compaction of the ensiled material. It was observed that most producers in the region do no forage planning by opening the silo before the minimum period for proper silage fermentation. The particle size observed for two groups was within expected range except for particles larger than 19mm. Concerning the presence of fungi in the silages were detected fungi of the genus Aspergilus, Cladosporium, Fusarium, Penicilium, Phoma, Pithomyces, Rhizopus and yeasts. The development of fungi of all genera was observed in groups one and three and the amount of fungi per extracts was random for all groups. Positive correlations were observed between certain genotypes of fungi with temperature, pH, particle size greater than 19 mm, mineral matter, NDF and FDA. The quality of maize silages produced in the western region of Paraná can be improved with greater investments in their preparation, such as sealing material, compaction time, regulation of the cutting machinery and evaluation of the cutting point.